Event segmentation in ADHD: neglect of social information and deviant theta activity point to a mechanism underlying ADHD - Christian Beste; Veit Roessner; Astrid Prochnow; Xianzhen Zhou; Foroogh Ghorbani; Bernhard Hommel (General Psychiatry)
Background Attention-deficit/hyperactivity disorder (ADHD) is one of the most frequently diagnosed psychiatric conditions in children and adolescents. Although the symptoms appear to be well described, no coherent conceptual mechanistic framework integrates their occurrence and variance and the associated problems that people with ADHD face.Aims The current study proposes that altered event segmentation processes provide a novel mechanistic framework for understanding deficits in ADHD.Methods Adolescents with ADHD and neurotypically developing (NT) peers watched a short movie and were then asked to indicate the boundaries between meaningful segments of the movie. Concomitantly recorded electroencephalography (EEG) data were analysed for differences in frequency band activity and effective connectivity between brain areas.Results Compared with their NT peers, the ADHD group showed less dependence of their segmentation behaviour on social information, indicating that they did not consider social information to the same extent as their unaffected peers. This divergence was accompanied by differences in EEG theta band activity and a different effective connectivity network architecture at the source level. Specifically, NT adolescents primarily showed error signalling in and between the left and right fusiform gyri related to social information processing, which was not the case in the ADHD group. For the ADHD group, the inferior frontal cortex associated with attentional sampling served as a hub instead, indicating problems in the deployment of attentional control.Conclusions This study shows that adolescents with ADHD perceive events differently from their NT peers, in association with a different brain network architecture that reflects less adaptation to the situation and problems in attentional sampling of environmental information. The results call for a novel conceptual view of ADHD, based on event segmentation theory.